Numerical Modelling of the Behaviour of Walls and Doors of 20 Ft ISO Containers through Real-Scale Explosion Tests - Seyth Amouzou; Guillaume Lecocq; Benjamin Le Roux; Emmanuel Leprette; Jos Planchard; Stéphane Charrondière; Laurent Mathieu (Chemical Engineering Transactions)
ISO containers are more and more used to shelter processes involving a potential explosion risk such as Battery Energy Storage Systems or hydrogen-based systems. With such systems, the containment can potentially lead to a risk of accumulation of flammable gases, which can result in explosions. An important part of the modelling strategy for predicting residual pressure effects of an internal explosion in an ISO container is the knowledge of the mechanical resistance of this structure subjected to blast load. In this context Ineris carried out hydrogen explosions tests in 20-foot ISO containers. The purpose was to collect comprehensive measurements related to the mechanical behaviour of the doors and walls. These complement other tests in the literature (Atanga et al., 2019) which have focused mainly on the explosion pressure inside the container. In parallel Ineris have developed a specific finite element numerical model using LS-DYNA software capable of predicting the dynamics response of a container – walls and doors – subjected to an internal explosion. The paper details the description of the numerical model and focuses on the comparison between simulations and tests in terms of displacements, strain and stresses levels as well as failure modes and opening time of the door.